On a subgroup of the affine Weyl group C˜4 - Muhammad A. Albar (International Journal of Mathematics and Mathematical Sciences)
We study a subgroup of the affine Weyl group C˜4 and show that this subgroup is a homomorphic image of the triangle group Δ(3,4,4).